Human Resource Management Transformation in The Digital Era: Innovations and Challenges In Startups - Anwar, Nursyam; Razak, Annisa Zhalila; Muhammad, A Fadel; Sukiman; Hamsyah (Economics and Business Journal (ECBIS), 2025)
The digital disruption era has significantly impacted startups, requiring them to adopt innovative Human Resource Management (HRM) strategies to remain competitive. This study examines HRM technology adoption, including AI-based recruitment, cloud-based HRIS, and digital collaboration tools, and the challenges that hinder their full implementation. Despite the benefits, budget constraints, lack of managerial support, and low digital competencyremain major obstacles. Using a qualitative descriptive approach, data were collected from Indonesian startups through in-depth interviews, observations, and document analysis. Findings indicate that startups with clear digital transformation roadmaps, strong leadership engagement, and structured employee training programs are more successful in integrating HRM technology. However, many startups still rely on manual HR processes, limiting efficiency and innovation. This study highlights that HRM should be a strategic function rather than an administrative task, focusing on technology-driven efficiency, digital upskilling, and cultural adaptation. To ensure sustainable growth, startups must prioritize digital innovation, workforce development, and managerial commitment in their HRM transformation.